Pengaruh Model STAD Terhadap Hasil Belajar Siswa Pada Pembelajaran PKn Di Kelas V SD - ameiftisa, riri; reinita, reinita; lubis, mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Abstract This research was undertaken as an attempt to assess the effect of cooperative learning model Student Teams Achievement Divisions (STAD) on the fourth grade students learning outcomes in Civic Education at SD negeri 31 Pasir Kandang Padang. This research adopted a quasi-experimental research design with The Nonequivalent Pretest-Posttest Contol Group Design. This research was done at SDN 31 Pasir Kandang Padang. The fourth grade students in class A was a control class consisted of 27 students while the fourth grade students in class B was an experimental class consisted of 28 students. The data were analyzed by using t-test. The result of the research revealed that the average score of the experimental group (72,75) which applied the cooperative learning model students teams achievement division (STAD) compared to the control class (62,48) showed better achievement. Based on the caculation of t-test, t-count (2,530) scored higher than t-table (2,006) for alpha 0,05. The results obtained from the data showed that there is more positive effect of cooperative learning model of STAD toward the fifth grade students learning outcomes in Civic Education at SDN 31 Pasir Kandang Padang. Keywords: STAD, Learning outcomes